Synthesis of Mo, W, and Mo- and W-Doped Multiwall VONTs via Sol-Gel and Hydrothermal Methods - Roya Rouhani; Hamid Reza Aghabozorg; Mohsen Asadi Asadabad; Hossein Aghabozorg (Journal of Chemistry)
Mo, W, and Mo and W were doped into multiwall vanadium oxide nanotubes. The syntheses were performed using sol-gel method followed by hydrothermal method. The synthesized samples were characterized by XRD, SEM, EDX, and TEM techniques. The XRD patterns of the synthesized samples indicated that Mo and W could be doped into VONTs totally up to 50%. The SEM and TEM images showed that the prepared samples have tubular and multiwall morphology and open ends.